Climate change operational framework 2017-2030 enhanced actions for low greenhouse gas emissions and climate resilient development. (Metro Manila, Philippines Asian Development Bank, 2017)
The Climate Change Operational Framework 2017-2030 positions ADB to facilitate, collaboratively and proactively, a regional shift toward a low greenhouse gas emissions and climate-resilient development path. The operational framework provides guidance across all ADB sector and thematic groups to strengthen climate actions, operationalizing ADB's commitment to provide at least
Keywords: Climate change mitigation -- Economic aspects; Environmental economics; Electronic books